Wage claims in the British private sector: 1979–2003. Issue 3 (19th May 2013) - Ingram, Peter; Rickman, Neil; Wadsworth, Jonathan
Abstract Wage claims have been an important feature of British industrial relations during the postwar period. They help set the boundaries within which wage negotiations take place and provide an insight into the conduct of negotiations, especially during periods of change in industrial relations. Despite this, claims remain an underinvestigated area. This article provides a unique investigation of the dimensions of wage claims over a period of free collective bargaining. The number of wage claims declined along with unionisation but, over a period of economic turbulence, the conduct of British wage setting began to change. We examine data on claims and investigate the influences on changes in those claims over time. We find that external factors (inflation, unemployment and legislative control of unions) were more prominent in shaping the development of claims than changes in the composition of groups who continued to post claims.